Ecological Value of Cemetery in Jakarta - Priharyaningsih, Dian; Hasibuan, Hayati Sari; Koestoer, Raldy (http://arl-faperta.ipb.ac.id/, 2019)
Cemetery Parks currently have a highly demand by urban community. The fact that settlement competing with the park. The study of green open space of cemetery was relatively limited to be observed. The objective of the study was to determine the potential of Cemetery Parks in absorbing carbon. The research was conducted in Tanah Kusir and Kampung Kandang cemetery parks. The methodology employed applied to Quadran typology. The balanced ecological assessment for both parks showed that the carbon absorbtion demonstrating significant results. And related trees as for Glodogan (Polyathea longifolia), Rambutan (Nephelium lappaceum) and Tanjung (Mimusops elengi), achieving gradual levels of carbon absorbtion.